Establishing a Deaf and American Sign Language Inclusive Residency Program. (18th February 2022) - Hill, Colin; Deville, Curtiland; Kiess, Ana; Narang, Amol; Ratnanather, Tilak; Bienstock, Jessica; Brinckerhoff, Loring; Hodukavich, Aaron; Anderson, Roberta; Alcorn, Sara; DeWeese, Theodore; Viswanathan, Akila; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Improving diversity in residency programs has been increasingly emphasized as a means to address gender, racial, and ethnic disparities in medicine. However, limited attention has been given to the potential benefits of training physicians with differences other than gender or race and ethnicity. Americans with a disability represent about 27% of the U.S. population, whereas 1%–3% of physician trainees report having a disability. In 2013, a national survey identified only 86 physicians or trainees reporting deafness or hearing loss as a disability. To date, there are no published strategies on how to create an inclusive program for Deaf trainees. Herein, the authors report on the development of a Deaf and American Sign Language (ASL) inclusive residency program that can serve as an academic model for other programs, in any medical specialty, seeking to create an accessible training program for Deaf physicians and that can be adapted for trainees with other disabilities. In March 2017, the radiation oncology residency program at Johns Hopkins University matched an ASL-signing Deaf resident who would begin the program in July 2018. In preparation, department leadership engaged key stakeholders and leaders within the university's health system and among the department faculty, residents, and staff as well as the incoming resident to create an ASL inclusive program. A 5-step transition process for the training program was ultimately developed and implemented. The authors focused on engaging the Deaf trainee and interpreters, engaging health system and departmental leadership, contracting a training consultant and developing oral and written training materials for faculty and staff, and optimizing the workspace via accommodations. Through collaborative preparation, a Deaf and ASL-signing resident was successfully integrated into the residency program. The proposed 5-step transition process provides an effective, engaging model to encourage other institutions that are seeking to employ similar inclusivity initiatives.